AB0108 Complications and formal pathogenesis of progressive systemic sclerosis. a retrospective study. (1st June 2001) - Bély, M; Szabó, T Szentjóbi; Kapp, P; Apáthy, Á; Stancikova, M; Istok, R
Abstract : Background: Progressive systemic sclerosis (SSc) is an autoimmune disorder anatomically characterised mainly by successive fibromuscular intimal proliferation of the blood vessels and by the increase of collagen fibres in various organs. The disease is, in general, characterised by the extent of the process and by the stage of the changes. Objectives: The aim of this study was to determine the main complications of SSc in various organs and histologically characterise the interstitial fibrotic process of SSc patients who died in different stages of their disease. Methods: A randomised autopsy population of 11 in-patients (female 10, average age: 53.6 years; male 1, age of 65 years at death), with clinically confirmed SSc was investigated retrospectively. 30–100 tissue samples from each patient were serially cut and stained with H-E, or picrosirius red F3BA. 1, 2 Results: In 10 of 11 cases, SSc was complicated by a wide spectrum of histological changes of the blood vessels. The lungs showed complex abnormalities such as vascular changes, interstitial pneumonitis, fibrosis or honeycomb-lungs in 6 of 11 patients. In the heart the complex vascular changes were accompanied by multifocal myocardiocytolysis and/or endo-myocardial fibrosis, which led to circulatory failure in 5 of 11 cases. Complex nephropathy in 10 of 11 patients was characterised by interstitial nephritis and/or fibrosis, by mesangioproliferative or membranous glomerulonephritis, and by multifocal cortical (tubular) necrosis. These renal changes led to uremia in 6 of 11 cases. Multifocal acute pancreatitis (of vascular origin) was observed in 6 of 11 cases. Different tissues and organs were affected to varying degrees, and the anatomic changes were simultaneously present in different stages at various sites. In all cases SSc was the basic disease which led to death. Conclusion: Anatomic changes could be seen in the early, advanced or late stages of the disease, essentially related to the chronology of the progressive sclerotizing process. SSc can be considered to be a progressive mulitfocal process characterised by simultaneous histological changes in different stages of their progression. In the course of the disease new foci form, which increase and become confluent, ultimately leading to diffuse, systemic interstitial sclerosis. (Supported by ETT Project T-11 226/99 of the Hungarian Ministry of Health). References: Sweat F, et al . Arch Path. 1964;78:69–72 Constantine VS, Mowry RW. J Invest Dermatol. 1968;50 :419–23